2018
DOI: 10.1109/tsp.2017.2775591
|View full text |Cite
|
Sign up to set email alerts
|

Bispectrum Inversion With Application to Multireference Alignment

Abstract: We consider the problem of estimating a signal from noisy circularly-translated versions of itself, called (MRA). One natural approach to MRA could be to estimate the shifts of the observations first, and infer the signal by aligning and averaging the data. In contrast, we consider a method based on estimating the signal directly, using features of the signal that are invariant under translations. Specifically, we estimate the power spectrum and the bispectrum of the signal from the observations. Under mild as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(151 citation statements)
references
References 81 publications
5
143
0
Order By: Relevance
“…On the other hand, autocorrelation analysis requires shorter computation time by summarizing the data as autocorrelation statistics with one pass over the data. We note that the distinct computational speeds for autocorrelation analysis and the EM algorithm is also observed in the related problem of multi-reference alignment [8], [14]. The difference in run time and the similar reconstruction quality of the two methods at low SNR make autocorrelation analysis the preferred approach for large datasets.…”
Section: Numerical Experimentsmentioning
confidence: 75%
“…On the other hand, autocorrelation analysis requires shorter computation time by summarizing the data as autocorrelation statistics with one pass over the data. We note that the distinct computational speeds for autocorrelation analysis and the EM algorithm is also observed in the related problem of multi-reference alignment [8], [14]. The difference in run time and the similar reconstruction quality of the two methods at low SNR make autocorrelation analysis the preferred approach for large datasets.…”
Section: Numerical Experimentsmentioning
confidence: 75%
“…Below, we start with p = 2. The PSWFs are eigenfunctions of the truncated Fourier transform and are given in polar coordinates by 5 ψ k,q (r, ϕ) = 1 √ 8π α k,q R k,q (r)e ιkϕ , r ≤ 1, 0, r > 1, (31) where the range of k, q is determined by Eq. (8) in [24], the R k,q are a family of real, one-dimensional functions and the α k,q are scaling factors which will be dened in the next section.…”
Section: F2 Autocorrelation Derivationmentioning
confidence: 99%
“…Thus, we proceed as follows: for each position i in the micrograph I, we extract the corresponding patch of size (2P − 1) × (2P − 1), expand it in the discretized PSWFs as in (36), and collect the a k,q as per (34) to constitute the second-order autocorrelation of the micrograph. 5 A dierent normalization is used in [24].…”
Section: F2 Autocorrelation Derivationmentioning
confidence: 99%
“…For the cryo-EM setup, assuming perfect particle picking and no CTF, it was shown that the sample complexity depends on the distribution of rotations: for uniform distribution the sample complexity scales as 1/SNR 3 (that is, the structure is determined by the third moment), while for generic non-uniform distribution the second moment suffices, and thus the sample complexity scales as 1/SNR 2 [11], [77]. Similar results were derived for simpler setups, for instance, when a discrete signal is acted upon by cyclic shifts (as shown in Figure 7) [22], [3], [11].…”
Section: A Multi-reference Alignmentmentioning
confidence: 61%